STRATEGI ADAPTASI NELAYAN DI DESA ALUE NAGA DALAM MENGHADAPI DAMPAK PERUBAHAN IKLIM - Elly Susanti; Mujiburrahmad Mujiburrahmad; Aurum Sahlida (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
The purpose of this study is to look at the climate change felt by fishermen in Alue Naga Village and identify economic adaptation strategies undertaken by fishermen in Alue Naga Village in dealing with the effects of climate change. The study was conducted by means of observing the observation of activities carried out directly to the location of the study of the research object using the interview method with a questionnaire that was processed using a Likert Scale and New Seven Tools. The results showed that fishermen in Alue Naga Village strongly agree with the perceived climate change that impacts on activities and affects their survival as fishermen who depend their lives on the sea. Fishermen feel climate change and are aware of the impacts caused by interviews through a questionnaire that found that fishermen have not fully adapted to the impacts of climate change. The improvement strategy using the new seven tools produces the improvement strategy by making efforts to foster a culture of understanding climate change that impacts the fishing community’s welfare.